Global Comparative Study on REDD+ phase 4 - Knowledge for action to protect tropical forests and enhance rights - Center for International Forestry Research (Center for International Forestry Research, 2021)
This three-year project (2021–2023) builds on CIFOR and partners’ long-term Global Comparative Study (GCS) on REDD+ since 2009, which has produced science-based information, analysis and tools to promote effective, efficient and equitable (3E) outcomes in REDD+ implementation, including secure rights and livelihoods for Indigenous Peoples and local communities.